2014
DOI: 10.1051/0004-6361/201424477
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of VLBI radio source catalogs

Abstract: Aims. I checked the consistency of recent astrometric radio source catalogs obtained by geodetic very long baseline radio interferometry (VLBI) with the second realization of the International Celestial Reference Frame (ICRF2), released in 2009, which is the most accurate astrometric catalog currently available. Methods. The catalogs were compared to the ICRF2 in terms of radio source coordinates, global second-degree deformations, and error distribution. Results. All catalogs were found to be consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Lambert (2013) assessed the axis stability of ICRF2 to be of 20 µas and reported that there has been no noticeable deformation in ICRF2 since 2009. Similar results are presented in Lambert (2014) showing that almost all catalogs from different IVS analysis centers are consistent with respect to ICRF2 within 20 µas, except some catalogs showing significant orientation angles of ∼40 µas. These works showed that the VLBI catalogs were generally consistent within several tens of µas.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Lambert (2013) assessed the axis stability of ICRF2 to be of 20 µas and reported that there has been no noticeable deformation in ICRF2 since 2009. Similar results are presented in Lambert (2014) showing that almost all catalogs from different IVS analysis centers are consistent with respect to ICRF2 within 20 µas, except some catalogs showing significant orientation angles of ∼40 µas. These works showed that the VLBI catalogs were generally consistent within several tens of µas.…”
Section: Introductionsupporting
confidence: 85%
“…The monitoring and maintenance of the ICRF have been undertaken in previous works, for example, Gontier et al (2001), Feissel-Vernier et al (2006), Sokolova & Malkin (2007), Lambert (2014). These works usually involve comparison of the radio source positions provided in the regular VLBI solutions from different International VLBI Service (IVS) analysis centers.…”
Section: Introductionmentioning
confidence: 99%
“…An accurate CRF opens the doors to millimeterlevel geodetic measurements (e.g., Earth rotation), insights into the Earth internal structure (e.g., Mathews et al 2002), and testing of General Relativity and alternative theories with VLBI (Le Poncin-Lafitte et al 2016, and references therein). The arrival of the Gaia Celestial Reference Frame (Gaia-CRF2, Gaia Collaboration et al 2016) -the first time that one can compare two independent CRF realizations with similar high accuracies -also allows comparisons between the positions of the common objects at several frequencies, bringing insights into the physics of quasars (e.g., Kovalev et al 2017), reference frames (e.g., Lambert 2014), and complex structures made of one or several black holes (e.g., Roland et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…2). The parameter D 3 is directly connected to the source declination, as it describes a glide toward the z-axis and thus is susceptible to many modeling and analysis choices during the processing of the VLBI data and linked to the so-called declination bias (e.g., Lambert 2014, and references therein). This term describes an artificial displacement of the sources toward the poles and is mainly associated with the asymmetry of the VLBI network.…”
Section: Extended Quality Assessment Of Input To Combinationmentioning
confidence: 99%